Retentionist in chief William Howard Taft and the question of Philippine Independence, 1912-1916 - Burns Adam D. (Philippine Studies: Historical and Ethnographic Viewpoints, 2013)
Between 1900 and 1913, Republican William Howard Taft maintained a keen interest in preserving a US imperial connection with the Philippines. Following defeat in his presidential reelection campaign of 1912, Taft became the unofficial leader of a retentionist movement to stop the US Democratic Party from making any firm promise of future independence for the islands, which he saw as a policy of scuttle.? This article brings light to the underexplored role Taft played in this movement, which proved a marked contrast to the route the US ultimately took in its interventions across the globe in the twentieth century and beyond.